The influence of dioxines on endometriosis development - study review - Alicja Maria Ozga-Stachurska; Justyna Wójcik-Grudzień; Paulina Pawłowska; Martyna Rozenbajgier (Kazimierz Wielki University, 2022)
Introduction: Dioxins and dioxin-like polychlorinated biphenyls are considered to be among the most toxic to humans due to their persistence, resistance to degradation and chemical properties. Endometriosis is characterized by the presence of endometrial cells outside the uterine cavity showing secretory activity. It is one of the most common causes of pelvic pain and decreased fertility; is formed as a result of the action of hormonal and immune mechanisms. The exact etiology is unknown and multifactorial; risk factors for endometriosis include both family conditions and various environmental factors, including exposure to chemicals. The aim of the study:  Evaluation of the impact of dioxins on endometriosis development. Materials and methods: A research was performed using Pubmed, Google Scholar and ResearchGate; we made review and meta-analysis of the most relevant studies. Results: Dioxins can contribute to cancer development, which is well documented, as well as several conditions, such as sexual dysfunctions, oxidative stress and inflammation. Doxins have similar structure to steroid hormones, so their main target are male and female gonads, thyroid gland and other organs in which steroid hormones are produced. Conclusions: Endometriosis is a multifactorial disease, whereas dioxins are strong poisons that have an adverse effect on live organisms. Many epidemiological studies suggest that dioxins may significantly contribute to the development of endometriosis.